An introduction to enzyme and coenzyme chemistry - Bugg, Tim (Blackwell Science, 1997)
This text provides a concise introduction to the molecular basis of enzyme and coenzyme action from the perspective of organic chemistry, and also discusses the major classes of enzymatic processes.